Perancangan Aplikasi Pencatatan Keuangan Menggunakan Appsheet Studi Kasus Pada Karang Taruna Berdikari Ngasem Utara - Wicaksono, Titis Aditya Putra; Edi, Sri Winarso Martyas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The Kaskita financial recording application is an application intended for the North Ngasem Independent Youth Organization. This application is expected to help organizations in managing finances. This research aims to evaluate the benefits of using this application in facilitating organizational financial management. Through application development methodology and analysis of organizational needs, this research presents a comprehensive design process and successful implementation of the Kaskita application. The evaluation results show that this application can run as needed to facilitate recording, tracking and analysis of organizational finances, as well as increasing transparency and accountability in fund management. The addition of financial report features is necessary for application perfection, because financial reports provide a comprehensive picture of the financial condition of a company or individual. The practical implications of this research are recommendations for further development of this application, as well as strategic implementation for optimizing financial management at the Karang Taruna organizational level.